Perbandingan Motivasi Sembuh saat Masuk Rawat Inap antara Pasien Dewasa dengan Hipertensi, Diabetes Melitus, Stroke, Tuberkulosis - Anderson, Elisa; Manoppo, Arlien J (NUTRIX, 2026)
Chronic diseases such as hypertension, diabetes mellitus (DM), stroke, and pulmonary tuberculosis (TB) remain a major health burden in Indonesia, making patient motivation to recover an important aspect of successful therapy. This study aims to analyze differences in recovery motivation upon admission to the hospital among adult patients with these four chronic diseases. The study design uses a quantitative analytical comparative cross-sectional approach with 175 respondents selected by convenience sampling. The variable of recovery motivation was measured using a Likert-scale recovery motivation questionnaire. Univariate analysis showed a high overall mean motivation (mean 90.02), with the highest mean in stroke and hypertension patients, followed by DM and TB. The Kruskal–Wallis test showed no significant difference in recovery motivation between disease types (p=.131). It was concluded that the recovery motivation of chronic disease patients upon admission tended to be high and relatively equal, so that disease type was not a major distinguishing factor. It is recommended that nurses integrate recovery motivation assessment and intervention into the nursing care of all chronic disease patients through strengthening therapeutic communication, education, family involvement, and psychosocial support from the beginning of care. Penyakit kronis seperti hipertensi, diabetes melitus (DM), stroke, dan tuberkulosis paru (TB) masih menjadi beban utama kesehatan di Indonesia, sehingga motivasi sembuh pasien menjadi aspek penting keberhasilan terapi. Penelitian ini bertujuan untuk menganalisis perbedaan motivasi sembuh saat masuk rawat inap pada pasien dewasa dengan empat penyakit kronis tersebut. Desain penelitian menggunakan pendekatan kuantitatif analitik komparatif cross‑sectional dengan 175 responden yang dipilih secara convenience. Variabel motivasi sembuh, diukur dengan kuesioner motivasi sembuh yang berskala Likert. Analisis univariat menunjukkan rata-rata motivasi keseluruhan tinggi (mean 90,02), dengan mean tertinggi pada pasien stroke dan hipertensi, diikuti DM dan TB. Uji Kruskal–Wallis menunjukkan tidak terdapat perbedaan bermakna motivasi sembuh antar jenis penyakit (p=,131). Disimpulkan bahwa motivasi sembuh pasien penyakit kronis pada saat masuk rawat inap cenderung tinggi dan relatif setara, sehingga jenis penyakit bukan faktor pembeda utama. Direkomendasikan agar perawat mengintegrasikan asesmen dan intervensi motivasi sembuh dalam asuhan keperawatan semua pasien penyakit kronis melalui penguatan komunikasi terapeutik, edukasi, pelibatan keluarga, dan dukungan psikososial sejak awal perawatan.